2000
DOI: 10.1002/1096-9071(200007)61:3<311::aid-jmv5>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

93G, a novel sporadic strain of hepatitis E virus in South China isolated by cell culture

Abstract: The nucleotide sequence of Hepatitis E virus (HEV) serous isolates (G-9 and G-20) from Guangzhou, South China, which has been reported previously, are divergent significantly from those of other reported HEV isolates. In order to investigate more extensively the Guangzhou isolate, the 93G strain was isolated from the faecal sample of the same individual as G-9 by A549 cell culture and identified immunologically and by molecular biological techniques. The results showed that strain 93G could be propagated in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Four cell lines (PLC/PRF/5, Huh-7, Caco-2, and HepG2/3CA) that replicated the transfected genome efficiently and A549 cells, which had been reported to support HEV infection (10,30), were inoculated with a titered stool pool of Sar55 virions. Cells in a 12-well plate at about 50% confluency were inoculated with 12,600 MID 50 for an approximate multiplicity of infection of 1 MID 50 per 20 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cell lines (PLC/PRF/5, Huh-7, Caco-2, and HepG2/3CA) that replicated the transfected genome efficiently and A549 cells, which had been reported to support HEV infection (10,30), were inoculated with a titered stool pool of Sar55 virions. Cells in a 12-well plate at about 50% confluency were inoculated with 12,600 MID 50 for an approximate multiplicity of infection of 1 MID 50 per 20 cells.…”
Section: Resultsmentioning
confidence: 99%
“…A group in China has reported the propagation of HEV in cultures of A549 human lung cells, but these results have not been confirmed elsewhere (10,30). HEV has been shown to infect primary cynomolgus hepatocytes and PLC/PRF/5 cells, but replication in these systems is so inefficient that reverse transcription-PCR (RT-PCR) is required to document it (16,25).…”
mentioning
confidence: 99%
“…However, we identified a novel sporadic strain (G9, G20 and 93G; GenBank accession number X87307 and X87306 and AF145208, respectively) isolated from patients in Guangzhou, a city in southern China, which is different from the prototypic isolates (Huang et al, 1995;Wei et al, 2000). Since this divergent variant was reported, some novel isolates from patients in the United States (US isolates) and from northern China (CT1) were also found to be distinct from the reported isolates (Schlauder et al, 1998;Wang et al, 1999Wang et al, , 2000.…”
Section: Introductionmentioning
confidence: 86%
“…Abbreviations representing the four genotype HEV isolates are given below and the GenBank accession numbers of the isolates and references are given in parentheses: Burmese prototype BUR1 (M73218) (Tam et al, 1991) and BUR2 (D10330) (Aye et al, 1993); Pakistan (Sar-55) PAK (M80581) (Tsarev et al, 1992); Chinese epidemic isolates CH1 or Xinjiang isolate (D11092) (Aye et al, 1992), CH2 or KS2 isolate (l25547/l25595) (Yin et al, 1994); CH3 or Hebei isolate (L08816/M94177) (Bi et al, 1994); CH4 or Uigh 179 (D11093) (Uchida, 1993) and Chinese divergent isolate found in Guangzhou, southern China (G9 X87307, G20 X87306, 93G AF145208) (Huang et al, 1995;Wei et al, 2000) and in northern China CT1 (AJ272108) (Wang et al, 2000); Indian fulminant hepatitis isolate IND1 (X98292) (Ansari et al, 2000) and IND2 or Mad isolate (X99441) (Arankalle et al, 1999); the Mexican prototype MEX (M74506) ; the US human isolates USP1 (AF060668) (Schlauder et al, 1998) and USP2 (AF060669) ; US swine isolate USSW (AF082843) (Meng et al, 1997); the Japanese isolates JAP1 (AP003430) (Takahashi et al, 2001) and JAP2 (Suzuki et al, 2002). The nucleotide sequences were aligned and compared using DNASIS computer software (Version 7.0).…”
Section: Phylogenetic Analysis Of Hev Genementioning
confidence: 99%
“…Propagation of HEV in vitro has been attempted in various cell lines (Divizia et al, 1999;Huang et al, 1992;Kazachkov et al, 1992;Meng et al, 1997;Wei et al, 2000), but an efficient cell culture system has not been developed. Several research groups have established infectious cDNA clones of HEV, which were observed to replicate in non-human primates or pigs (Emerson et al, 2001(Emerson et al, , 2004bGraff et al, 2005;Huang et al, 2005Huang et al, , 2007Panda et al, 2000).…”
mentioning
confidence: 99%